EVALUATION OF POLYCYCLIC AROMATIC HYDROCARBONS IN PORK MEAT PRODUCTS OBTAINED IN TRADITIONAL SYSTEMS IN ROMANIA - TĂBĂRAN, Alexandra; CORDIŞ, Ionuţ Vlad; BECZE, Anca; DAN, Sorin Daniel; REGET, Oana-Lucia; ILE, Gheorghe; PUSTA, Dana Liana; PASCA, Ioan; BORZAN, Mihai Marian; MIHAIU, Marian (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The aim of this study was to determine the polycyclic aromatic hydrocarbons (PAH) levels in the smoked meat products obtained in the traditional system in Romania. The importance of this study resides in the fact that these compounds are known to be carcinogenic, and their levels should be strictly monitored to ensure the safety of the consumers. Until now, no study was performed in Romania that addresses this issue in the traditional pork meat products. The study was performed on 60 meat products samples (sausages, bacon, ham) taken from a certified traditional meat processing unit but also from retail units that delivered industrially processed meat products. The method used in the detection of the 15 PAHs analysed was HPLC. Our results showed that the highest percent of total PAHs is found in the traditionally obtained smoked bacon and the lowest in industrially produced pork meat sausage. None of the samples examined exceeded the limit imposed by the European legislation for benzo[a]pyrene (BaP), but the smoked bacon revealed higher values for PAH4 than the allowed limit. Following this study, we suggest that a more careful attention should be paid to all factors and apply such smoking conditions that result in the lowest possible contamination with PAH in pork meat products obtained in the traditional system in Romania.